Risk factors for blood loss in liver resection surgery: An Institutional Review. - Khan, Muhammad Shadab; Khan, Muhammad Attaullah; Saba, Ayesha; Amir, Sana; Anwar, Abdul Wahid (International Journal of Endorsing Health Science Research, 2021)
Background: Surgical resection of the primary or metastatic liver lesions is the treatment of choice for patients with resectable tumors. Identifying and managing preoperative and intraoperative risk factors responsible for increased blood loss during liver resection is extremely important. Therefore, the present study aims to identify preoperative and intraoperative risk factors associated with blood loss during liver resection. Methodology: A retrospective cross-sectional study was conducted on 72 patients who underwent liver resection for resectable primary and metastatic liver lesions at the Department of Surgical Oncology Hepatobiliary Unit, Shaukat Khanum Memorial Cancer Hospital, and Research Center Lahore. The study continued from October 2014 to July 2017, and data were collected from hospital records, including demographic, biochemical, and perioperative variables. Results: Out of the total 38 patients, 52.8% were female, with a mean age of 40.59 ± 21.66 years at the time of surgery. The results after multivariate analysis conclude two independent risk factors responsible for significant blood loss of more than 1000 milliliters during liver resection. These factors include liver cirrhosis, where the odds ratio is 7.96 with 95% CI (1.00-63.31) and P-value of 0.05 and operative time of 390 minutes where odds ratio is 8.94 with 95% CI (2.28-36.48) and P-value of 0.02. Conclusion: The risk factors associated with increased intraoperative blood loss during liver resections in our population are mainly associated with preoperative parameters, including positive viral serology and radiologically proven liver cirrhosis. In contrast, intraoperative factors were intravenous fluid administration and operative time.